Online growth options for retailers : three essays on domestic and international growth strategies with online retailing - Schu, Matthias (Springer Gabler research., 2017)
Matthias Schu examines three main topics in his research: The intention of store-based retail and wholesale companies to open up an own online channel, factors determining the foreign market selection behavior of online retailers as well as factors affecting the speed in the internationalization process of online retailers. New insights for retail research and management are presented and contribute to existing knowledge; the study is valuable for academic researchers and for practitioners who are interested in a thorough analysis of online retailing from a strategic and theoretical perspective. Contents Foreign Market Selection, Resource and Path Dependency of Internationalization Decisions of Online Retailers Internationalization Speed of Online Retailers Imitability of Online Shops, Strategies and Concepts Establishment of Online Shops by SME Retailers and Wholesalers as an Additional Sales Channel Target Groups Researchers, lecturers and students in the disciplines of Online Retailing, E-Commerce, Retailing, Channel Management, Strategy, and Marketing Managers and E-Commerce strategy responsibles in Retail, Online Retail and Strategy Companies, SME Founders, and Consultants About the Author Dr. Matthias Schu currently works as Senior Strategy Consultant at a consulting company. Besides consulting and advisoring in the field of Strategy, Innovation and Management, he also works as author, advisor and speaker in the fields of Retailing, E-Commerce and Internationalization Strategies.